Targeted Anterior Cervical Epidural Blood Patch in a Patient with Spontaneous Intracranial Hypotension - Ravindra Singh Shekhawat; Ming Hui Yong; Si Ying Julienne Keong; Kunihiko Chen; Chow Wei Too; Shahul Hameed (Case Reports in Neurological Medicine)
A 45-year-old male was admitted with severe orthostatic headache secondary to spontaneous intracranial hypotension. He had the site of cerebrospinal fluid (CSF) leakage identified at the anterolateral aspect of the C7-T1 spinal level. He first underwent a conventional posterior-approach cervical epidural blood patch (EBP) which provided immediate relief to the patient’s symptoms; however, his symptoms recurred two days later. To better target the anterolateral leakage site, we employed an anterior-approach EBP under computed tomography (CT) guidance. After this attempt, the patient experienced complete relief of his symptoms, and the headache eventually resolved.